Modelo pedagógico para la interactividad de las ciencias técnicas Aproximación conceptual (2016)
The solution to a problem not is necessarily the answer favorable, is the support, the method of knowledge with which occurs the response. This research reconciles a method of knowledge that thrives by integrating various methods of knowledge from the integration of Sciences around a common problem solving and in the perspective of providing technical and technological solutions. The pedagogical model, which allows to understand the educational phenomenon arising from the integracion-articulacion of the various sciences and their methods of knowledge, must rebuild the teaching of technical sciences from a superior syllabus, and from this, to give shape to the linearity of the academic syllabus.